Correlation of allergic serological markers with bronchiectasis severity in high-resolution computed tomography chests of patients with allergic bronchopulmonary aspergillosis: A retrospective study - Padamati Advytha; Karniha Balasubramanian; Ancila P; Sowmya P; Nalini Jayanthi Nagesh (Asian Journal of Medical Sciences, 2025)
Background: Allergic bronchopulmonary aspergillosis is a hypersensitivity reaction to Aspergillus fumigatus that leads to airway inflammation and bronchiectasis in susceptible individuals. Elevated immunoglobulin E (IgE), specific IgE, and eosinophilia correlate with disease severity; however, their precise relationship with high-resolution computed tomography (HRCT) findings remains unclear. Aims and Objectives: This study aimed to correlate allergic serological markers with the severity of bronchiectasis in HRCT chest using a bronchiectasis score on patients with allergic bronchopulmonary aspergillosis (ABPA). Materials and Methods: This retrospective observational study included data from 50 patients at SRM Medical College, Hospital and Research Centre, Kattankulathur, from June 2022 to June 2024. The medical records of patients with ABPA were reviewed for symptoms, history of asthma, steroid use, allergies, and comorbidities. The data included absolute eosinophil count (AEC), total IgE, specific IgE for A. fumigatus, and HRCT findings. The correlation between serological markers and bronchiectasis severity was analyzed using the bronchiectasis score. Results: The highest proportion (36%) of patients were aged ≤30 years, with a male predominance (58%). Cough was the most common symptom (96%), and hemoptysis was seen in 8% of study subjects. Asthma severity and serological markers were correlated with the bronchiectasis score, where asthma severity showed a strong correlation with the bronchiectasis score (r=0.807, P<0.05). AEC (r=0.473), total IgE (r=0.447), and specific IgE (r=0.504) levels showed moderate positive correlations. Conclusion: A good correlation exists between allergic serological markers and bronchiectasis severity in patients with ABPA, as observed on HRCT. Higher AEC, total IgE, and specific IgE levels against A. fumigatus were associated with more severe bronchiectatic changes.